Feeding Time Interval on Growth and Yield Seeds of Two Varieties of Potato Plants (Solanum Tuberosum L.) on Aeroponics Systems - Ramadhani (Indoensia), Nail Barkah; Farid (Indoensia), Noor; Wahyudiningsih (Indoensia), Tri Suwarni (JURNAL VIGOR, 2023)
Potato plant (Solanum tuberosum L.) is an important food source as well as an alternative food. Potato productivity in Indonesia experienced a decline in production in 2020, due to the limited availability of quality seeds. Efforts to overcome these problems with seed production using an aeroponic system. The time interval for nutrition in potato aeroponics was controlled by a timer. Use of appropriate varieties in aeroponics in order to increase yields. The aim of the study was to determine the time interval for giving nutrition, the best variety, and the interaction between the time interval for giving nutrition and the kinds of varieties. The research was carried out at the Greenhouse of the Faculty of Agriculture, Tidar University (1,200 masl) from February-May 2022 using a factorial (2x2) completely randomized design (CRD). Factor I interval of nutrition includes 5 minutes off and 15 minutes on (I1), 10 minutes off and 15 minutes on (I2). Factor II varieties include varieties of granola L. (V1) dan tedjo MZ. (V2). The data were analyzed using ANOVA and continued with the BNT test. The results showed that the interval (I2) was best for plant height and number of leaves, while for (I1) the best results were on fresh tuber. Two varieties of potato (Solanum tuberosum L.) had no effect on all observation parameters. The interaction between the interval of nutrition and the variety was responded the same to all observation parameters